Barriers to Behavioural Change and JQ HIV and AIDS in Africa (2011)
Communication is central to any health intervention programme worldwide. This paper documented various communication and learning related theories that can be applied to change at risk behaviour facilitating the spread of HIV and AIDS in Africa. It also looks at barriers to behaviour change.